1995
DOI: 10.1007/bf00128383
|View full text |Cite
|
Sign up to set email alerts
|

Novel sophorose lipids from microbial conversion of 2-alkanols

Abstract: Using glucose/rac. 2-alkanols as carbon sources for the cultivation of Candida bombicola novel types of sophorose lipids were isolated as major products.Among all lipophilic constituents 2-alkanol was found as the major hydrophobic moiety (> 75%) involved in three new sophorose lipids differing only in the degree of acetylation of the sophorose. Additional monooxygenation of the alcohol leads to the incorporation of 2,(e-1)-alkandiol; glycolipids with up to four glucose units were obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…Brakemeier et al (1995Brakemeier et al ( , 1998a used secondary alcohols (C12-C16) as the lipophilic carbon source and observed direct incorporation for the majority of the substrate. Primary alcohols can be applied as well, but these tend to be largely metabolized in b-oxidation unless an adjusted medium with high glucose and yeast extract content is provided.…”
Section: Results and Discussion Fermentations Run On Already Hydroxylmentioning
confidence: 99%
See 1 more Smart Citation
“…Brakemeier et al (1995Brakemeier et al ( , 1998a used secondary alcohols (C12-C16) as the lipophilic carbon source and observed direct incorporation for the majority of the substrate. Primary alcohols can be applied as well, but these tend to be largely metabolized in b-oxidation unless an adjusted medium with high glucose and yeast extract content is provided.…”
Section: Results and Discussion Fermentations Run On Already Hydroxylmentioning
confidence: 99%
“…Despite these variations, the sophorolipid fatty acid tail is limited to 16 or 18 carbon atoms. This restricted length hampers the use of sophorolipids in certain cleaning purposes; molecules with a shorter fatty acid tail would broaden up the application range as this will cause a shift in the hydrophilic/hydrophobic balance of the molecule, resulting in better water solubility and in some cases improved surface lowering capacities (Brakemeier et al, 1995). Yet, these molecules are not readily obtained by a simple low cost fermentation process.…”
Section: Introductionmentioning
confidence: 99%
“…These alkyl sophorosides showed a better surface activity than the classical sophorolipids and lowered the surface tension of water from 72 mN m -1 to 31 mN m -1 . Furthermore, Brakemeier et al (1995Brakemeier et al ( , 1998b showed that other secondary alcohols, such as 2-tetradecanol or 2-hexadecanol and ketones with an even number of carbon atoms like 2-, 3-, and 4-dodecanone, can be converted to the corresponding alkyl sophorosides by C. bombicola.…”
Section: Structure Elucidation and Characterization Of Microbial 2-trmentioning
confidence: 99%
“…the co-substrate 2-dodecanone. By the use of 2-tetradecanol or 2-hexadecanol as co-substrate they obtained around 24 g l -1 alkyl sophorosides after 9 days of cultivation (Brakemeier et al, 1995). Since the 2-tridecanone cultivation was a preliminary experiment, there is potential for improvement, e.g.…”
Section: Cultivation With Co-substrates With An Odd Number Of Carbon mentioning
confidence: 99%
See 1 more Smart Citation